1999
DOI: 10.1007/s004260050043
|View full text |Cite
|
Sign up to set email alerts
|

The psychophysics of perceptual memory

Abstract: Psychophysical studies of short-term memory for attributes or dimensions of the visual stimulus known to be important in early visual processing--spatial frequency, orientation, contrast, motion--identify an early perceptual memory system. The proposed system, which may be part of the Schacter-Tulving perceptual representation system (PRS), is located early in the visual processing stream, prior to the structural description system responsible for shape priming but beyond primary visual cortex (V1), and consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
140
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 73 publications
17
140
2
3
Order By: Relevance
“…Bays, Catalao, & Husain, 2009;Bays & Husain, 2008), but individual stimuli can be retained with a high level of detail (Magnussen & Greenlee, 1999). Additionally, Fougnie, Suchow, and Alvarez (2012) have reported that the quality of visual memory varies within an individual, and this variability changes according to the number of stimuli that must be remembered (in their experiment, memory variability increased as the set size was expanded from one to three items, and from three to five items).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bays, Catalao, & Husain, 2009;Bays & Husain, 2008), but individual stimuli can be retained with a high level of detail (Magnussen & Greenlee, 1999). Additionally, Fougnie, Suchow, and Alvarez (2012) have reported that the quality of visual memory varies within an individual, and this variability changes according to the number of stimuli that must be remembered (in their experiment, memory variability increased as the set size was expanded from one to three items, and from three to five items).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, memory for simple visual attributes can be perfectly retained for periods exceeding 10 s (Magnussen, Greenlee, Baumann, & Endestad, 2010). Magnussen and Greenlee (1999) reported that memory for spatial frequency is as accurate at 10-30 s as it as at 1 s, challenging decay. VSTM for motion also appears to be resistant to temporal decay (Blake, Cepeda, & Hiris, 1997;Poom, 2012;Zokaei, Gorgoraptis, Bahrami, Bays, & Husain, 2011).…”
mentioning
confidence: 99%
“…several studies that show that the execution of a second task can interfere with memory for one or more stimuli that were presented several seconds earlier (Barrouillet et al, 2004(Barrouillet et al, , 2007Ricker & Cowan, 2010; see also Ueno, Allen, Baddeley, Hitch, & Saito, 2011), and there have also been several studies that found that a distractor can interfere with retention of a similar stimulus shown 1-5 s earlier (e.g., Magnussen & Greenlee, 1999;Magnussen, Greenlee, Asplund, Dyrnes, 1991;Vuontela, Rämä, Raninen, Aronen, & Carlson, 1999). An interesting and important difference between these findings and those of current experiments, however, is that the interference effects follow a markedly different time course.…”
Section: Relationship With Previous Findingsmentioning
confidence: 99%
“…More recent behavioral experiments showed impaired memory performance if a distractor, or memory mask, is presented up to 500 ms after presentation of the memory item (Magnussen et al, 1996;Jolicoeur and Dell'Acqua, 1998;Vogel et al, 2006). The distractor may interfere with the memory representation of the target stimulus, thereby affecting the window of consolidation more directly (Magnussen and Greenlee, 1999;Enns and Di Lollo, 2000).…”
Section: Introductionmentioning
confidence: 99%